Coca-Cola's MDCs : distribution effectiveness vs social responsibility? - Townsend, Stephanie (SAGE knowledge. Cases., 2016)
By June 2010, The Coca-Cola Company's micro distribution centre (MDC) network in Africa had proven to be incredibly successful. Coca-Cola had built up the network to distribute its products through small, independent local entrepreneurs to even smaller outlets, enabling the company to reach markets that were once difficult to access. Now social marketers were approaching Coca-Cola for permission to distribute their own products using the MDC network. Paul Fourie, group strategy and business planning director of Coca-Cola Eurasia and Africa, was charged with the task of finding the best way to move forward.